The Effect of Offline Assisted Learning Serli Practicum Module on Solar System Materials on Student Learning Motivation - Mawar Sari; Melyani Sari Sitepu; Azizah Azizah; Ratman Ratman; Nur Rahma Putri (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
The purpose of this study was to determine the effect of offline learning assisted by the Serli practicum module on the solar system material on the learning motivation of sixth-grade students of SD Inpres Lolu. The type of this research is quantitative research with experimental research type using a Quasi-experimental method with a Quasi-experimental design. The subjects in this study were students of class VI SD Inpres Lolu totaling 21 people. There were 11 experimental class students and 10 control class students. Data collection was carried out using a research instrument in the form of a questionnaire, and data analysis using prerequisite tests, namely normality test and homogeneity test and hypothesis testing using unpaired test sample t-test which was analyzed using SPSS Statistics version 25. Based on the results of this study showed a significant value of paired sample T-Test 0.000 <0.05 then accepts the Ha hypothesis and rejects Ho, meaning offline learning assisted by the Serli practicum module on the solar system material affects the learning motivation of sixth-grade students of SD Inpres Lolu.